Pemikiran Politik dan Kenegaraan Hasan Al Turabi dan Mahmoed Mohammed Thaha - Muhibbin Zuhri (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2004)
This study aims to analyze and compare the political thoughts and concepts of statehood of Hasan al-Turabi and Mahmoed Mohammed Thaha, two Muslim intellectual figures who have different views on Islam and politics. The method used is qualitative research with a descriptive-analytical approach and a comparative study of the works and ideas of both. The results show that al-Turabi emphasizes Islam as the basis of a modern and inclusive political system, while Thaha proposes a reinterpretation of Islamic teachings with a progressive and humanist approach. Their thoughts reflect differences in seeing the relationship between religion and the state, with al-Turabi supporting the integration of Islam in politics, while Thaha emphasizes separation to achieve social justice. This study provides new insights into the dynamics of Islamic political thought and its relevance in the contemporary political context.